PENGEMBANGAN MATERI AJAR KERAGAMAN FLORA DAN FAUNA TERINTEGRASI KEARIFAN LOKAL DI KELAS V MADRASAH IBTIDAIYAH - Hisyam, Fauziah; Suryani, Lilis; Baderiah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
The low understanding of students in the flora and fauna material of class V Madrasah Ibtidaiyah is a reference for researchers to develop teaching materials integrated with local wisdom. The purpose of this research is to analyze the needs of students, development design, validity and practicality of the teaching materials developed. The R&D method is the chosen method, Addie's development model includes the stages of Analysis, Design, Development, Implementation, Evaluation, with instruments of observation, interviews, questionnaires, and documentation. Using quantitative and qualitative data analysis as part of the stages of development so that the data obtained is more relevant. The results of this study are based on the need analysis of the need for new innovations in the design of teaching materials to improve students' understanding, the design of material development using Canva is sought to be interesting and creative so as to make it easier for students. The validation of the material involved three validator experts, the validation results showed a valid score of 75% from linguists, material experts with a score of 90% were very valid and design experts with a score of 75% were valid. In the practicality test process by teachers and students, good results were shown where teachers with a score of 100% practical and students with a score of 97% practical. Based on these results, the teaching materials developed are suitable for use in the learning process.